Construction of learning tools based on the sets approach to empower students' environmental literacy on ecological materials - Heny Pertiwi; Afandi Afandi; Eko Sri Wahyuni (JPBIO (Jurnal Pendidikan Biologi), 2021)
The development of learning tools with a SETS approach is considered important to foster student interest in learning and critical thinking as well as to instill and improve the level of environmental literacy of Indonesian students which is still relatively low. This study aims to determine the analysis of the needs of SETS-based learning tools, to know the process of developing SETS-based learning tools, and to determine the validity and reliability of SETS-based learning tools. The development in this study uses a 4-D model development with stages, namely define, design, develop, and disseminate. Then it is reduced to 3-D with the stages of define (defining), design (design), develop (development). This research produces a product in the form of learning tools, namely RPP (Learning Implementation Plan) and SETS-based modules. The lesson plans and modules that have been developed are then validated by five validators, namely three lecturers of Biology Education FKIP Untan, one teacher from MA Darul Ulum, and one teacher at SMAN 1 Rasau Jaya. The results of the validation of the learning tools were obtained and declared valid with the average acquisition of Aiken's V calculation of 0.84 with a minimum value of 0.80. The reliability of this learning device was tested using the ICC (Interclass Correlation Coefficient) technique with the help of the SPSS program. The reliability of the RPP obtained a result of 0.520 with a moderate category and there was an agreement between raters, while the reliability of the module obtained a result of 0.536 with moderate reliability and agreement between raters.